2002
DOI: 10.2320/jinstmet1952.66.7_745
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Analyses of Modified-Ausformed Medium-Carbon Steel with High Resistance to Hydrogen Embrittlement by Atomic Force Microscopy

Abstract: H d) and time to failure (t f) for the modified ausformed and tempered (MAQT) martensite and the conventional QT martensite with a tensile strength of 1580 MPa 5) .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…[24][25][26] This can be explained in terms of higher density of dislocations, 25) denser distribution of carbide particles, 25,26) and finer block structure 27) in the AF steels. The results in Figs.…”
Section: Tensile Propertiesmentioning
confidence: 99%
“…[24][25][26] This can be explained in terms of higher density of dislocations, 25) denser distribution of carbide particles, 25,26) and finer block structure 27) in the AF steels. The results in Figs.…”
Section: Tensile Propertiesmentioning
confidence: 99%
“…Precipitates on boundaries have been shown to play important roles in intergranular fracture mechanisms of tempered martensitic steels. 14,15,[19][20][21] For this reason, the authors quantified precipitate distribution separately for the entire microstructure and prior grain boundaries (intergranular).…”
Section: Changes In Microstructure Caused By Creep-fatigue 321 Distmentioning
confidence: 99%
“…The distribution of carbide precipitates in grain interiors and grain boundaries was quantitatively analyzed in terms of both number and size by specifying the locations of prior grain boundaries in a large visual field. [13][14][15] The authors also applied microstructural analytical methods to ferritic heat-resisting steels that were originally developed for carbon steels. Electropolished surfaces of 9 to 12 mass% Cr ferritic steel were observed under a field emission-type scanning electron microscope (FE-SEM), and thin films of these specimens were observed under a TEM.…”
Section: Introductionmentioning
confidence: 99%
“…Using atomic force microscopy (AFM), Hayakawa et al 6,7) observed in detail the microstructures of two types of low-alloy JIS-SCM440 steel-modified-ausformed, and quenched and tempered. They found that in the modified-ausformed steel, the density of cementite at the prior austenitic grain boundaries decreased owing to the refinement of martensitic blocks.…”
Section: Introductionmentioning
confidence: 99%